Ecology and Genomic Insights into Plant-Pathogenic and Plant-Nonpathogenic Endophytes - Günter Brader; Stéphane Compant; Kathryn Vescio; Birgit Mitter; Friederike Trognitz; Li‐Jun Ma; Angela Sessitsch (2017)
Plants are colonized on their surfaces and in the rhizosphere and phyllosphere by a multitude of different microorganisms and are inhabited internally by endophytes. Most endophytes act as commensals without any known effect on their plant host, but multiple bacteria and fungi establish a mutualistic relationship with plants, and some act as pathogens. The outcome of these plant-microbe interactions depends on biotic and abiotic environmental factors and on the genotype of the host and the interacting microorganism. In addition, endophytic microbiota and the manifold interactions between members, including pathogens, have a profound influence on the function of the system plant and the development of pathobiomes. In this review, we elaborate on the differences and similarities between nonpathogenic and pathogenic endophytes in terms of host plant response, colonization strategy, and genome content. We furthermore discuss environmental effects and biotic interactions within plant microbiota that influence pathogenesis and the pathobiome.